Interação entre a micrometeorologia e variabilidade espacial em diferentes alturas de dossel na Flona de Caxiuanã (Pa) - SIQUEIRA, Brenda Santos (2019)
The objective of this study was to determine the spatial variability inside the grid of PPBio in Caxiuanã (PA), studying the temperature and relative humidity at two heights in different topographic and canopy heights. Was selected a site with topographic variation, where they were placed “datalogger” for automatic measurements of temperature (°C) and relative humidity (%) on the plateau and in the lowland in various heights: above the ground level (0.50 m) , 2.0 m, 4.0 m, 6.0 m, 8.0 m, 10.0 m, 12.0 m, 14.0 m, 16.0, 18.0 m and 20.0 m . Measurements were made at the end of the period with less rainfall (December 2009), and at the end of the rainy season (June 2010), where the measurements took place on two consecutive days in each period were analyzed, and the data collected each minute. The results revealed the existence of high variation of temperature and relative humidity for the different canopy heights. When the occurrence of precipitation events, the canopy height of tallest responded quickly, however the lower altitudes only respond to prolonged rain events. The data reveal that there is probably a big influence on the bay Caxiuanã temperature and relative humidity at all levels of canopy and topography for a few moments still not well understood. The results reveal the existence of high variation of temperature and relative humidity for the different canopy heights. Upon the occurrence of precipitation events, levels of canopy but next cup responds quickly, though the heights near the ground but only respond to prolonged rain events. The data reveal that there is probably a big influence on the bay Caxiuanã temperature and relative humidity for a few moments still not well understood.